Assessment of sesquiterpene lactones isolated from Mikania plants species for their potential efficacy against Trypanosoma cruzi and Leishmania sp. - Laurella, Laura Cecilia (2017)
Four sesquiterpene lactones, mikanolide, deoxymikanolide, dihydromikanolide and scandenolide, were isolated by a bioassay-guided fractionation of Mikania variifolia and Mikania micrantha dichloromethane extracts. Mikanolide and deoxymikanolide were the major compounds in both extracts (2.2% and 0.4% for Mikania variifolia and 21.0% and 6.4% for Mikania micrantha respectively, calculated on extract dry weight). Mikanolide, deoxymikanolide and dihydromikanolide were active against Trypanosoma cruzi epimastigotes (50% inhibitory concentrations of 0.7, 0.08 and 2.5 µg/mL, for each compound respectively). These sesquiterpene lactones were also active against the bloodstream trypomastigotes (50% inhibitory concentrations for each compound were 2.1, 1.5 and 0.3 µg/mL, respectively) and against amastigotes (50% inhibitory concentrations for each compound were 4.5, 6.3 and 8.5 µg/mL, respectively). By contrast, scandenolide was not active on Trypanosoma cruzi.